Interclusion: Epistemological and Didactic Approaches for the Transformation of Contemporary Education - Román-Soto, David (2024)
Objective. This essay aims to reflect on the pressing issue of migration in the Latin American region, and particularly Chile, a country that has experienced a considerable increase in the influx of foreign population into its territory in recent years. Discussion. This analysis addresses the challenges and possibilities that migration presents to socio-educational transformation, from a new epistemic perspective of inclusion and interculturality. This perspective favors the full integration of foreign students into diverse educational contexts. Although inclusion and interculturality are relevant to the current reality and theoretically enrich each other, they do not engage in dialogue concerning public policy and, therefore, do not promote the development of a new local and diverse identity. Conclusion. From an intersectional perspective, this article proposes the concept of interclusion, which emerges from the interrelation of inclusion, interculturality, and identity. Interclusion serves as a response to reflection, analysis, and development of pedagogical and learning practices that are attentive to multicultural realities. It also serves as a response to the constant challenge of improving pedagogical and didactic processes to advance in the construction of Latin American knowledge.